2013
DOI: 10.1021/ma4000368
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition Temperature of Polymer–Nanoparticle Composites: Effect of Polymer–Particle Interfacial Energy

Abstract: Numerous studies have shown that the glass transition temperature, T g , of polymers may change visibly upon addition of even small amounts of nanoparticles. In this study, we examine the effect of polymer−nanoparticle interfacial energy on this phenomenon in nanocomposite films containing polystyrene-grafted nanoparticles mixed with polystyrene homopolymer at low particle loadings. A previous experiment showed that the interfacial energy of this system modulates with the grafting density of the grafted polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…Therefore, some free volume spaces for the dangling polystyrene chains within matrices may be created as a resultant of MCM 41 nanoparticles aggregation which results in decrement of T g values. Numerous studies have dem onstrated that the glass transition temperature of poly mers can be changed upon addition of low content of nanoparticles [48,49]. In this context, reduction of T g values by increasing nanoparticles into the polymer matrix are plenty reported.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some free volume spaces for the dangling polystyrene chains within matrices may be created as a resultant of MCM 41 nanoparticles aggregation which results in decrement of T g values. Numerous studies have dem onstrated that the glass transition temperature of poly mers can be changed upon addition of low content of nanoparticles [48,49]. In this context, reduction of T g values by increasing nanoparticles into the polymer matrix are plenty reported.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the results obtained by different authors reveals that the glass transition temperature of the composite is largely determined by factors such as: The production process (e.g., a sol‐gel method or a polymerization‐filling technique) . The method of stabilization of the nanoparticles in the polymer bulk (surface modification by low‐ or high‐molecular compounds) . The chemical structure of the nanoparticle surface, which provides the possibility of chemical bond formation and an adsorption interaction between the matrix and particle . The size of the particles and their aggregates . …”
Section: Introductionmentioning
confidence: 99%
“…In particular, ellipsometry studies 35 indicate that shifts from the bulk T g are the result of the interface (air/PS interface in PS films), viscosity measurements on thin films of low-M n PS have shown modifications even when the thickness is well above R EE , 36 and experiments with homopolymer brushes have shown that the amount of deviation is determined by the interfacial energy. 37,38 Thus, a simplified model, as shown in Scheme 2, for each block component consists of a region (V Int ) of finite size …”
Section: ■ Introductionmentioning
confidence: 99%